Malaria vaccine in India: need and choice - Saranya, Rajaram; Sahanaa, Chandar; Mohandass, Roselin (International Journal Of Community Medicine And Public Health, 2022)
Malaria is a major public health problem in India. India’s varied geography and diverse climatic conditions from tropical monsoon in the south to temperate in the north, favor the distribution of vectors and species of the malaria parasite. Malaria in India takes several forms, including forest/ tribal malaria, urban malaria, industrial malaria, and plains malaria. P. falciparum and P vivax species contribute to the majority of malarial cases and deaths in India.